Implementation of Learning Nagham Al-Qur’an in The Art of Reading The Qur'an for Children and Adolescent at LPTQ in Medan City - Baihaki Harahap; Abd. Mukti; Haidir Haidir (Jurnal Basicedu, 2022)
This study aims to describe the implementation of nagham al-Qur'an learning in the art of reading the Qur'an for children and adolescents at the Tilawatil Qur'an Development Institute (LPTQ) Medan City. Furthermore, this study also analyzes people's perceptions of the nagham al-Qur'an in Javanese style. In the process, this research uses a qualitative approach with a descriptive study method. Data was collected using interview, observation, and documentation techniques. Furthermore, the data is analyzed in stages, starting from a preliminary study, conducting research, analyzing data, drawing conclusions, to the stage of reporting research results. The results of this study indicate that the basic nagham al-Qur'an learning material for children at LPTQ Medan City includes tajwid and makhraj letters, while for teenagers it is added to routinely study 4 (four) nagham al-Qur'an. The teaching is carried out regularly using the qiro'ati, sima'i, halaqah, and demonstration methods. The various types of nagham al-Qur'an include hijaz, bayati, shoba, jiharka, nahawan, sika, and others. The learning media used include microphones, speakers, and voice recording devices. Furthermore, there are supporting factors for learning nagham al-Qur'an, namely adequate facilities, systematic learning activities, the seriousness of students repeating learning at home, coaches and trainers who are experts in their fields, and support from the Medan City government. While the inhibiting factors include health factors, lack of concentration of students, and limited time allocation.